2013
DOI: 10.7314/apjcp.2013.14.11.6869
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Tamoxifen and Tranilast on VEGF and MMP-9 Regulation in Cultured Human Breast Cancer Cells

Abstract: Background: Vascular endothelial growth factor and matrix metalloproteinases are two important factors for angiogenesis associated with breast cancer growth and progression. The present study was aimed to examine the effects of tamoxifen and tranilast drugs singly or in combination on proliferation of breast cancer cells and also to evaluate VEGF and MMP-9 expression and VEGF secretion levels. Materials and Methods: Human breast cancer cell lines, MCF-7 and MDA-MB-231, were treated with tamoxifen and/or tranil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…Many studies have demonstrated that MMP-9 (Hassan et al, 2012;Zhang et al, 2012;Akdeniz et al, 2013;Asuthkar et al, 2013;Darakhshan et al, 2013;Li et al, 2013), ERK1/2 (Romano et al, 2012), KIT (Kim et al, 2011) and PTEN are considered to be the potential targeted genes of miR-494. In present study, BAG-1 is predicted as the targeted gene of miR-494 by using bioinformatics tools TargetScan, PicTar, and Miranda.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that MMP-9 (Hassan et al, 2012;Zhang et al, 2012;Akdeniz et al, 2013;Asuthkar et al, 2013;Darakhshan et al, 2013;Li et al, 2013), ERK1/2 (Romano et al, 2012), KIT (Kim et al, 2011) and PTEN are considered to be the potential targeted genes of miR-494. In present study, BAG-1 is predicted as the targeted gene of miR-494 by using bioinformatics tools TargetScan, PicTar, and Miranda.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs are overexpressed not only by glioma cell lines but also by the tumor vasculature, suggesting a relevant role in angiogenesis induction and regulation (Liotta et al, 1991;Hanahan and Folkman, 1996). MMP9 are overexpressed also in many other tumors, such as in osteosarcomas (Jin et al, 2013), breast cancer (Darakhshan et al, 2013), cholangiocarcinoma (Kidoikhammouan et al, 2013), human fibrosarcoma cell (Yahayo et al, 2013), which all are overexpressed, suggesting a relevant role in tumor angiogenesis, growth, and invasion. Our results showed that MMP9 expressions were markedly decreased in Lenti-radixin cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…It was found to significantly reduce VEGF/VPF-induced vascular permeability [130]. Tranilast had an anti-angiogenic effect on lung carcinoma cells [91], and suppressed VEGF expression and secretion in breast cancer cells [131]. Furthermore, it had anti-angiogenic or anti-VEGF-induced chemotactic effects in autoimmune disease models [7].…”
Section: Angiogenesismentioning
confidence: 99%